Metal oxide semiconducting interfacial layers for photovoltaic and photocatalytic applications - Elumalai, Naveen Kumar; Vijila, C.; Jose, R.; Uddin, A.; Ramakrishna, S. (Springer Berlin Heidelberg, 2015)
The present review rationalizes the significance of the metal oxide semiconductor (MOS) interfaces in the field of photovoltaics and photocatalysis. This perspective considers the role of interface science in energy harvesting using organic photovoltaics (OPVs) and dye-sensitized solar cells (DSSCs). These interfaces include large surface area junctions between photoelectrodes and dyes, the interlayer grain boundaries within the photoanodes, and the interfaces between photoactive layers and the top and bottom contacts. Controlling the collection and minimizing the trapping of charge carriers at these boundaries is crucial to overall power conversion efficiency of solar cells. Similarly, MOS photocatalysts exhibit strong variations in their photocatalytic activities as a function of band structure and surface states. Here, the MOS interface plays a vital role in the generation of OH radicals, which forms the basis of the photocatalytic processes. The physical chemistry and materials science of these MOS interfaces and their influence on device performance are also discussed.